The University of the Philippines Los Banos during the Japanese occupation (1941-1945) challenges, responses and experiences - Diestro, Dwight David A. (2013)
Founded in 1909, UP Los Banos is one of the constituent universities in the University of the Philippine System. It is identified primarily with two pioneering units: the College of Agriculture and School of Forestry. In the history of institution, the Second World War is a watershed a conjuncture that defined the direction of the University. The period of 1941 to 1945 provided both challenges and opportunities. UP Los Banos was allowed to operate during the Japanese occupation because of its relevance to national interest. Food production was a priority. The scientific spirit was also strong. The quality of leadership was a source of strength. Through the physical dimensions of the University life as it were continued. Classes were held and students received their degrees. However, enrolment went down and the number of faculty declined. Atrocities happened during the last week of February 1945. Most of the buildings, equipment and specimens were destroyed. As an institution of higher learning. UP Los Banos was able to adapt within the exigencies of Japanese Occupation.